THE CALL OF THE WILD AND THE PEN: THE LIFE AND LITERARY LEGACY OF JACK LONDON - Rahimova Dilnora (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the tumultuous life and prolific literary career of Jack London, one of America’s most influential and commercially successful writers of the early 20th century. The study examines how London’s personal experiences—ranging from intense poverty and maritime adventures to his participation in the Klondike Gold Rush—shaped his unique literary style. By blending elements of Naturalism, Social Darwinism, and Socialism, London created timeless masterpieces that captured the raw struggle between humanity, nature, and society.